PEDAGOGICAL SUPPORT FOR THE EFFECTIVE ORGANIZATION OF SPIRITUAL AND MORAL EDUCATION IN HIGHER EDUCATIONAL INSTITUTIONS AND THE CONTENT OF ITS MODERNIZATION - Tursunboyeva, Nargiza Komilovna (SCIENCE and SOCIETY, 2026)
This article examines the interrelated regulatory, pedagogical, methodological, logistical (including informational), and personnel aspects of pedagogical support for the effective organization of spiritual and moral education in higher education institutions. In today’s context, these components require updating in both content and form.